Bortezomib, Ifosfamide, Carboplatin, and Etoposide in a Patient with HIV-Negative Relapsed Plasmablastic Lymphoma - Mehmet Akce; Elaine Chang; Mohammad Haeri; Mike Perez; Christie J. Finch; Mark M. Udden; Martha P. Mims (Case Reports in Hematology)
Plasmablastic lymphoma (PBL) is a rare subtype of diffuse large B cell lymphoma (DLBCL), often associated with HIV infection. We present a case of a 53-year-old HIV-negative man with untreated hepatitis C viral infection who presented with abdominal pain and lymphadenopathy. Lymph node and bone marrow biopsies were consistent with plasmablastic lymphoma. He had partial response (PR) to 6 cycles of EPOCH but disease progressed seven weeks later. Repeat biopsy was consistent with plasmablastic lymphoma. Three cycles of bortezomib, ifosfamide, carboplatin, and etoposide (B-ICE) chemotherapy resulted in a partial response (PR). Five months later, he presented with widespread lymphadenopathy and tumor lysis syndrome with circulating blasts. Flow cytometry revealed a different population of lymphoma cells, this time positive for CD5, CD19, CD20, and CD22, with dim expression of CD45 and CD38. The patient died on the first day of ESHAP chemotherapy. There are no treatment recommendations or standard of care for plasmablastic lymphoma. A literature search yielded 10 cases in which bortezomib was administered in either HIV-positive or HIV-negative PBL. Six reported a partial response, 3 reported a complete response, and 1 was a near-complete response. Bortezomib, in combination with chemotherapy, may be an effective treatment option in PBL as reported here.